New data on Marantelophus iranicus and Empitrombium makolae (Acari: Erythraeidae, Microtrombidiidae) - Mahnaz Kohansal; Sara Ramroodi; Javad Noei; Ehsan Rakhshani (Persian Journal of Acarology)
Additional morphometric and other data are provided for larvae of Marantelophus iranicus (Trombidiformes: Erythraeidae) collected ectoparasitic on Carpocoris coreanus (Hemiptera: Pentatomidae) and from soil and litter (off-host) in South Khorasan Province (Chahkand, Giuk, Khan and Shahrestanak villages, Birjand), Iran. A key to the genera of larval Abrolophinae and larval species of Marantelophus of the world is presented. Moreover, the family Chironomidae is recorded as the host of Empitrombium makolae (Trombidiformes: Microtrombidiidae) for the first time.